2011
DOI: 10.1007/s10552-011-9737-4
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and alcohol drinking increased the risk of esophageal cancer among Chinese men but not women in a high-risk population

Abstract: Although the association for esophageal cancer with tobacco smoking and alcohol drinking has been well established, the risk appears to be less strong in China. To provide more evidence on the effect of smoking and alcohol consumption with esophageal cancer in China, particularly among Chinese women, a population-based case–control study has been conducted in Jiangsu, China, from 2003 to 2007. A total of 1,520 cases and 3,879 controls were recruited. Unconditional multivariate logistic regression analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 29 publications
4
51
0
Order By: Relevance
“…Dey and Caderbaum (2006) reported that alcohol increase the ROS pool in smokers. There are reports that support the view that alcohol and smoking together increases risk of cancer (Vioque et al, 2008;Ming et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Dey and Caderbaum (2006) reported that alcohol increase the ROS pool in smokers. There are reports that support the view that alcohol and smoking together increases risk of cancer (Vioque et al, 2008;Ming et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…BMI was statistically lower 5 years before 2 A bowl commonly used in the local area. 3 Mean intake per week among all consumers was categorized into four levels based on quartiles: Q1 (<22.7 g), Q2 (>22.7-90.8 g), Q3 (>90.8-151.4 g) and Q4 (>151.4 g). 4 Salted meat intake was included in the model as a continuous variable.…”
Section: Resultsmentioning
confidence: 99%
“…2 Mean intake per week among all consumers was categorized into four levels based on quartiles: Q1 (<22.7 g), Q2 (>22.7-90.8 g), Q3 (>90.8-151.4 g) and Q4 (>151.4 g). 3 Additional adjustment for smoking (pack-years). 4 Additional adjustment for alcohol drinking (average ethanol intake per week).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations